PERAN LEMBAGA DAKWAH FAKULTAS LSMI AL-MADANI FISIP UNRI DALAM PEMBERDAYAAN POTENSI KADER DAKWAH - Jopanda, Sandewa; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Campus political life represents a democratic system or a miniature state that causes power struggles and domination. Da'wah institutions have long been known to dominate student organizations at the University of Riau. The proof is that many Da'wah cadres are involved and have strategic positions in student organizations. Al-Madani as one of the Da'wah institutions implements superior cadre so that its cadres can be empowered. The purpose of this study is to identify, analyze, and explain the cadre process, basic system interactions, forms of empowerment of potential cadres, the role of Al-Madani and the behind-the-scenes actors or interventions that manage Al-Madani's cadre. This study used a descriptive qualitative method and involved 3 informants who were the core administrators of Al-Madani for 2 periods, and 1 key informant who was the Advisory Board of the Al-Madani LSMI. Determination of informants using purposive sampling technique. Data collection techniques were carried out by observation, interviews, and documentation. The results of this study indicate that there is a systematic and structured role in the cadre and empowerment of Al-Madani cadres which has a positive impact on the existence and sustainability of the organization. The role of the Al-Madani LSMI is as a forum for organization and a medium for friendship (identification), a forum for understanding Islam and potential development (classification and education), a tactical tool for campus politics (selection, distribution, and mobilization) and, a decisive reference for Da'wah cadres (instructions and evaluation) are implemented and realized by the Al-Madani LSMI. Keywords: Cadre, Da'wah, Role, Empowerment, Potential